Comparison of male and female patients with amnestic mild cognitive impairment: Hippocampal hyperactivity and pattern separation memory performance. Issue 1 (3rd August 2020) - Corona‐Long, Caitlin A.; Tran, Tammy T.; Chang, Elizabeth; Speck, Caroline L.; Gallagher, Michela; Bakker, Arnold
Abstract: Introduction: Recent studies have suggested that sex confers a differential risk in the incidence and prevalence of Alzheimer's disease (AD) thought to be the result of the increased lifespan of women compared to men. However, other factors may contribute to risk beyond the effect of increased lifespan. Methods: This study examined the role of sex in hippocampal hyperactivity localized to the dentate gyrus (DG)/CA3 subregion of the hippocampus and associated episodic memory impairment, considered a characteristic feature of AD in patients with amnestic mild cognitive impairment (aMCI). Results: While participants with aMCI showed decreased memory performance and increased activation in the DG/CA3 when compared to controls, no significant sex‐related differences in performance or activation were observed. Discussion: Although other factors may contribute to sex differences in the prevalence of AD these findings show that no sex differences are observed in hippocampal dysfunction characteristic of the aMCI phase of AD.